2013
DOI: 10.1021/jp406679s
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Quantum Dots of CdTe and Reduced Graphene Oxide: Investigation through Cyclic Voltammetry and Spectroscopy

Abstract: Cyclic voltammetry has been used to investigate the interaction between reduced graphene oxide (r-GO) and CdTe quantum dots (Q-CdTe). For that, the composite of Q-CdTe with r-GO (r-GO-CdTe) was prepared by carrying out the reduction of graphene oxide and the synthesis of Q-CdTe simultaneously, in a single bath. r-GO-CdTe was characterized by UV–visible, steady state fluorescence, time-resolved fluorescence, X-ray diffraction (XRD), Raman, and transmission electron microscopy (TEM). Cyclic voltammetry was emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 35 publications
5
44
1
Order By: Relevance
“…The band structure parameters of various quantum dots as a function of size [28] (size quantization effect) and composition [25] (band gap bowing effect) have been estimated by CV and matched very well with the independent results obtained by photoelectron spectroscopy in air (PESA) [25,36]. Interaction of graphene with quantum dots also have been studied and the results have been further corroborated by time resolved photoluminescence (PL) spectroscopy [29]. Even though there are lot of convenience to use CV to estimate the band edge parameters, sometimes nature of solvent pose some limitation on the available potential window especially in case of wide band-gap materials.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…The band structure parameters of various quantum dots as a function of size [28] (size quantization effect) and composition [25] (band gap bowing effect) have been estimated by CV and matched very well with the independent results obtained by photoelectron spectroscopy in air (PESA) [25,36]. Interaction of graphene with quantum dots also have been studied and the results have been further corroborated by time resolved photoluminescence (PL) spectroscopy [29]. Even though there are lot of convenience to use CV to estimate the band edge parameters, sometimes nature of solvent pose some limitation on the available potential window especially in case of wide band-gap materials.…”
Section: Introductionsupporting
confidence: 70%
“…Both these techniques involve major instrumentation and tedious sample preparation and thus out of reach to many chemists for the routine applications. Recently, our group [25][26][27][28][29] and many others [30][31][32][33][34][35] have demonstrated that these parameters can equally accurately estimated by bench top approach like cyclic voltammetry (CV). Cathodic and anodic peaks in the CV analysis are associated to the electron transfer mediated through conduction and valence band-edges, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…This method has been successfully applied to study CdS, CdSe, CdTe, CdS x Se 1-x , as well as Cu 2-x Se y S 1-y and CZTSeS NCs in this respect. [64][65][66][67][68][69][70][71][72] The CV method is based on the transient analysis of gaining and losing electrons on the electrode's surface. The injection of electrons to the conduction band minimum (CBM) generates the reduction current, while the extraction of electrons from the valence band maximum (VBM) results in an oxidation current.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis adopted here was based on methods used to synthesize CdTe-ZnTe alloys in aqueous medium [29] and the strategy was found to be successful to form Cd 1-x Mg x Te nanocrystal alloys. We evaluated first the effect of different initial Cd:Mg proportions (0.25:0.75, 0.5:0.5 and 0.75:0.25) on the photoluminescence (PL, inset at the left side of Fig.…”
Section: Synthesis Of CD 1-x Mg X Te Nanocrystalsmentioning
confidence: 99%